Validity of a structure sensor-based anthropometric measurement: performing a pilot study - Katovic, D.; Mišigoj-Durakovic, M.; Bušic, A. (Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2019)
Development of new technologies is offering possibilities to overcome "traditional" limitations of anthropometric measures and enable the production of a new generation of simple, high-speed, inexpensive, highly defined and precise scanners for superficial body imaging. This study is an attempt to determine the metric characteristic of the instrument (BodyRecog PRO) which technology is based on the method of deep infrared 3D-scanning (Structure sensor). Reliability of the digitally obtained anthropometric measures was tested in the process of relating them with the measures obtained via the traditional anthropometric quantification.